KETERAMPILAN BERPIKIR KRITIS DAN PEMAHAMAN KONSEP SISWA KELAS IV MELALUI PEMBELAJARAN RADEC PADA MATERI GAYA - Wita Puspita Dewi, - (2022)
Critical thinking and understanding of science concepts are very important for students in the 21st century, but in reality students' ability to think critically and understanding concepts still looks low. Because the learning process in schools tends to be teacher-centered, so students cannot freely hone their knowledge and abilities in learning activities. The RADEC learning model is a new breakthrough in the world of education in the context of achieving 21st century competencies. The purpose of this study is to find out how the implementation of learning, critical thinking skills and understanding of students' concepts through the RADEC learning model on style material. This research uses quantitative research methods. The participants in this study were fourth grade students at SDN Cipaku 02 Bandung Regency. The instruments used for data collection are observation and test guidelines. Data collection was carried out using observation guidelines during learning activities, while tests of critical thinking skills and conceptual understanding were given at the beginning and end of learning. Then they were analyzed and processed quantitatively to find out the results. The results showed that the RADEC model was effectively used in learning style material in fourth grade elementary school. This is indicated by the value of Sig. (2-tailed) = 0.000 this means Sig (2-tailed) (0.000) <0.05 that after the results of the hypotests test shows the RADEC model is a learning model that can improve students' critical thinking skills and conceptual understanding.